CONSUMPTION BEHAVIOR MODEL OF SANTRI AT MODERN PUTRI BOARDING SCHOOL, MALANG REGENCY, EAST JAVA - Riski, Dita Suci Novia; Nasikh, Nasikh; Wulandari, Dwi (Universitas Indraprasta PGRI, 2025)
This study examines the consumption behavior model of santri (Islamic boarding school students) at a Modern Putri Boarding School in Malang Regency, East Java, as well as analyzing its impacts and the pesantren's policies regarding it. This qualitative research, employing an iterative thematic inquiry method, was conducted using in-depth interviews, observation, and documentation studies. The findings indicate that santri consumption behavior is complex, influenced by the interaction between personal needs, accessibility, preferences shaped by trends and peer influence, and the ability to manage pocket money. The impacts of this behavior encompass financial, social, and psychological aspects. Financially, santri show variations in pocket money management, with some successfully saving while others experience difficulties. There are differences in daily expenditures within the boarding school and during student visits, indicating a